A heterogeneous reaction strategy towards the general synthesis of 2D non-layered nanomaterials. Issue 11 (20th May 2022) - Qin, Wenjing; Liu, Hao; Liu, Jiahui; Yuan, Jiangbo; Wei, Cong; Xu, Qun
Abstract : A general heterogeneous reaction strategy was proposed to pave a novel avenue to the 2D non-layered nanomaterials. Abstract : 2D non-layered materials exhibit various exotic physical and chemical features that are distinctly different from their layered counterparts, but a general synthesis approach is still lacking for their intrinsic isotropic chemical bonds. In this study, a diffusion-controlled heterogeneous interfacial reaction strategy was proposed to drive the 2D anisotropic growth of the non-layered crystals. 2–3 nm thick single-crystalline hexagonal CdS nanosheets were obtained via a facile gas–liquid reaction. The diffusion of the Cd and S precursors was impeded by the interphase boundary and only the ultrathin interfacial region had sufficient reactants to afford the chemical conversion, leading to the naturally confined 2D anisotropic growth of the CdS crystals. Besides, this universal approach can be easily extended to synthesize other 2D non-layered materials, and various ultra-thin non-layered nanosheets, such as orthorhombic Bi2 S3, monoclinic CuO, anatase TiO2 and cubic Al2 O3, have been successfully obtained by designing appropriate heterogeneous reaction systems. Our results provide a robust access to the 2D non-layered materials that may lead to a significant proliferation of the 2D family.